Allosteric crosstalk between peptide-binding, transport, and ATP hydrolysis of the ABC transporter TAP - Gorbulev, Stanislav (The National Academy of Sciences, 2001)
The transporter associated with antigen processing (TAP) is essential for intracellular transport of protein fragments into the endoplasmic reticulum for loading of major histocompatibility complex (MHC) class I molecules. On the cell surface, these peptide–MHC complexes are monitored by cytotoxic T lymphocytes. To study the ATP hydrolysis of TAP, we developed an enrichment and reconstitution procedure, by which we fully restored TAP function in proteoliposomes. A TAP-specific ATPase activity was identified that could be stimulated by peptides and blocked by the herpes simplex virus protein ICP47. Strikingly, the peptide-binding motif of TAP directly correlates with the stimulation of the ATPase activity, demonstrating that the initial peptide-binding step is responsible for TAP selectivity. ATP hydrolysis follows Michaelis–Menten kinetics with a maximal velocity V(max) of 2 μmol/min per mg TAP, corresponding to a turnover number of approximately 5 ATP per second. This turnover rate is sufficient to account for the role of TAP in peptide loading of MHC molecules and the overall process of antigen presentation. Interestingly, sterically restricted peptides that bind but are not transported by TAP do not stimulate ATPase activity. These results point to coordinated dialogue between the peptide-binding site, the nucleotide-binding domain, and the translocation site via conformational changes within the TAP complex.